The importance of adiponectin in the human body - Aneta Szafraniec-Porada; Dominik Porada; Michał Konopeklo; Daria Przybylska; Małgorzata Pucułek (Kazimierz Wielki University, 2018)
Adipose tissue produces various types of proteins, including adipocytokines, which is why it should be treated as an endocrine organ. Adiponectin is one of the most important adipokines in the human body. We distinguish three factions of adiponectins: low molecular weight (LMW), middle molecular weight (MMW) and high molecular weight (HMW). The purpose of this article is to attempt to summarize the current state of knowledge regarding adiponectin, in particular its role in the human body. Adiponectin significantly influences the metabolism of carbohydrates by stimulating the activity of AMPK and PPAR-α through the AdiopoR1 receptors, which results in an increase in uptake and oxidation of glucose in cells. The literature has repeatedly demonstrated a negative correlation of serum adiponectin concentrations in relation to the BMI index, insulin and triglyceride levels, HOMA-IR and blood pressure. Decreased adiponectin levels have been demonstrated in such diseases as obesity, type 2 diabetes, hypertension, ischemic heart disease or in patients after a stroke. The significant effect of this adipocytokine on the reduction of inflammation, lipid metabolism and effect on the vascular endothelium is of key importance in the process of atherosclerotic plaque formation. In conclusion, the correct concentration of adiponectin is important for maintaining proper function of the whole organism. It affects numerous metabolic processes, mainly the metabolism of carbohydrates and lipids. It has antiatherogenic and anti-inflammatory properties. Due to the low concentrations of adiponectin found in patients with chronic diseases, including type 2 diabetes, there is a need for further research to determine the exact effect of adiponectin on these morbidities.